Evaluation of coffee drying costs: pre-drying on concrete terrace and complementary drying in co-current and counter-current flow dryer - Martin, Samuel (2011)
The study of drying costs is an important tool to be considered when deciding on an adequate drying system. One needs to consider the energy needed for air heating, electrical energy needed to run the fans, energy to transport the product, labor costs, maintenance costs, depreciation, interest rates and breakdown costs. The objective of this study was to determine the total drying cost per bag of dry coffee beans (Coffea arabica L.), by drying processed coffee in the form of pulped cherries, with pre-drying on a concrete yard followed by complementary drying in a developed prototype dryer with concurrent and countercurrent flows. The dryer was constructed of a metallic frame and plates, with a static capacity of 1.55 m3. An initial concurrent drying stage was separated from a second counter-current flow drying stage by a repose chamber. Two treatments were applied: a) Treatment 01: 12 hours of intermittent drying with intermittent rotation and 12 hours of rest, with air temperature of 45 °C and rotation of the beans every 90 minutes for drying (for a period of 10 minutes each); b) Treatment 2: 12 hours of intermittent drying with continuous rotation and 12 hours of rest, with air temperature of 70 °C. Coffee quality was determined via a sensorial analysis (cup-test). It was concluded that: The fixed cost of the multiple flow dryer was the principal component in the total cost of drying, principally since it was treated as a prototype; Increase in the drying capacity of the system with application of treatment 02 (with continuous rotation), in relation to treatment 01 (with intermittent rotation), drastically reduced total drying costs; The results obtained from treatment 01 demonstrate its economic infeasibility, due to the elevated drying costs encountered for the proposed system under the conditions in which this study was performed.